Risk factors for morphoea disease severity: a retrospective review of 114 paediatric patients. (1st April 2014) - Pequet, M.S.; Holland, K.E.; Zhao, S.; Drolet, B.A.; Galbraith, S.S.; Siegel, D.H.; Chiu, Y.E.
Summary: Background: Morphoea is a rare fibrosing disease of the skin and subcutaneous tissue with an unpredictable disease course, running the spectrum from mild skin involvement to severe disfigurement or extracutaneous complications. Objectives: Our objective was to describe the natural history of paediatric morphoea and determine patient variables that were associated with severe disease. Patients and methods: We conducted a retrospective chart review of patients with morphoea seen in one paediatric hospital system. Information about demographics, clinical characteristics, disease course and treatment were collected. Statistical analysis was performed using appropriate univariate tests and a multivariable model. Results: One hundred and fourteen patients met study inclusion criteria. The female : male ratio was 2·6 : 1, and the median age of onset was 7 years old. There were 55 patients (48%) with linear morphoea, 38 patients (33%) with circumscribed morphoea, 12 patients (11%) with generalized morphoea, and nine patients (8%) with mixed morphoea. Neurological symptoms and joint involvement were present in 27 subjects (24%). Extracutaneous manifestations occurred in 38% of subjects with linear morphoea, compared with 15% with generalized morphoea and 3% with circumscribed morphoea ( P = 0·0001). Thirty‐six per cent of children with disease onset prior to 10 years of age and 5% of children with disease onset after 10 years of age had extracutaneous manifestations ( P = 0·0002). Both linear morphoea and early‐onset disease were significantly associated with extracutaneous involvement in a multivariable model. Conclusions: Children with linear morphoea and disease onset before 10 years of age should be monitored closely for extracutaneous manifestations and need early treatment with systemic medications to prevent disease complications.